Upaya Penanggulangan Tindak Pidana Pembuangan Bayi Di Wilayah Hukum Polres Bangli - I Made Indra Sastrawan; I Made Minggu Widyantara; Ida Bagus Gede Agustya Mahaputra (Fakultas Hukum Universitas Warmadewa, 2022)
Child is someone who is not yet 18 years old, including children who are still in the womb. All actions that can interfere with children's rights can be punished according to the applicable law. Currently, there are many cases of infant disposal in Indonesia, such as what happened in Banjar Lumbuhan, Susut Village, Susut District, Bangli Regency. Then a problem arises. This research aims to find out what factors are the causes of the criminal act of throwing away babies in the Bangli Police Legal Area. How are the efforts of the police to deal with the criminal act of disposing of babies in the Bangli Police Legal Area. The method of research uses an empirical legal research type, namely conducting field research at the Bangli Police Police office, through interviews with the support of several laws and regulations that apply in several books as a support. There are various factors behind the disposal of a baby such as a person's age, not ready for marriage, shame, lack of attention from family, being ostracized by society, getting pregnant outside of marriage, being abandoned by a pre-marital partner, the impact of globalization. Efforts to control infant disposal are divided into preemptive, preventive and repressive efforts.